IDENTIFIKASI DAMPAK INTERAKSI OBAT ANTIHIPERTENSI TERHADAP TEKANAN DARAH PADA PASIEN GERIATRI HIPERTENSI YANG DIRAWAT INAP DI RSUD DR SOEDARSO PONTIANAK - Egida Rachmadani; Eka Kartika Untari; Muhammad Akib Yuswar (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Hypertension is one of cardiovascular diseases in geriatrics. Hypertensive geriatric patients require a combination of more antihypertensives to achieve blood pressure targets, it can cause high risk of polypharmacy. Polypharmacy in hypertensive geriatric patients is at high risk of drug interactions that can affect their blood pressure. This study aims to identify the interactions of antihypertensives based on mechanism and severity and also to determine whether there is a change in blood pressure caused by drug interactions in geriatric hypertensive inpatients at RSUD Dr Soedarso on January – June 2019. Data were collected retrospectively from 38 patients’ medical records, using total sampling technique. Data were analyzed descriptively using E-book Stockley’s Drug Interaction and Drug Interaction Checker on medscape.com, drugs.com. There were 28 patients (73%) who may experience drug interactions with a total of 85 cases. Drug interactions with moderate severity and pharmacodynamic interaction mechanism often occur in a row were 61 cases (72%) and 79 cases (93%). There were a decrease and increase blood pressure, which in a row were 23 and 4 patients. The decrease of patients’ blood pressure estimated caused by synergistic drug interactions of antihypertensives and adjustment of each drug dose that has potential to increase blood pressure.